Synthetic strategies for the preparation of γ-phostams: 1,2-azaphospholidine 2-oxides and 1,2-azaphospholine 2-oxides - Xu, Jiaxi (Beilstein Journal of Organic Chemistry, 2022)
γ-Phostams include γ-phosphonolactams and γ-phosphinolactams and their fused derivatives, phosphorus analogues of γ-lactams. They are 1,2-azaphospholidine 2-oxides and 1,2-azaphospholine 2-oxides and important biological five-membered azaphosphaheterocycles. They have been prepared through two major strategies of cyclizations and annulations. Cyclizations achieve ring construction through the formation of any bond in the ring, while annulations build the ring via [4 + 1] and [3 + 2] fashions with the simultaneous formation of two bonds. The review includes the synthesis of 1,2-azaphospholidine and 1,2-azaphospholine 2-oxides/sulfides and their fused derivatives.
Keywords: azaphospholidine; azaphospholine; phosphonolactam; γ-phosphonolactam; phosphinolactam; γ-phosphinolactam; γ-phostam